Hubungan Perilaku Pencarian Pengobatan dengan Tuberkulosis Paru di Sulawesi Utara - Ernawati, Kholis; Kardiana, Aan; Duarsa, Artha Budi Susila; Muhammad, Faisal (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2017)
Background: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Health seeking behavior is one of the factors that influence the incidence of pulmonary tuberculosis. The purpose of this study to determine the relationship with the incidence of treatment-seeking behavior of Tuberculosis in North Sulawesi province based on basic health research in 2010. Method: The design of this study used a descriptive approach correlative. The research sample is total sampling of all basic health research respondent data in 2010 in the province of North Sulawesi aged ≥15 years amounts to 2319 respondents. The analytical method used univariate and bivariate. Results: The results showed the incidence of pulmonary TB in North Sulawesi province is 11 people (14.1%), and respondents who continued treatment of TB program eight (10.3%). Conclusion: There was a relationship between the incidence of treatment-seeking behavior of pulmonary TB (p=0.037).